Underestimation of velocities by color doppler in valvular regurgitation - Perry, Gilbert J.; Myers, Jerry G.; Anayiotos, Andreas (My University, 1995)
The accuracy of Color Doppler (CD) in measuring flow velocities in Valvular Regurgitation is assessed in an in-vitro setup and compared with a theoretical model. A steady flow circular model of 3,5,10 mm is used. The flow field is numerically calculated using Fluid Dynamics International Evanston (FIDAP). Basing from the results, it is concluded that CD provides reliable velocities in large regurgitant orifices, however, it should be used in caution in smaller orifices where significant underestimation should be expected.
Keywords: Cardiovascular system; Hemodynamics; Fluid dynamics; Biomechanics